Acetophenone glycosides from the roots of Euphorbia fischeriana and their inhibitory effects against Mycobacterium smegmatis. (March 2017) - Huang, Shan-Shan; Li, Ping; Zhang, Bao-Jing; Deng, Sa; Zhang, Hou-Li; Sun, Cheng-Peng; Huo, Xiao-Kui; Tian, Xiang-Ge; Ma, Xiao-Chi; Wang, Chao
Graphical abstract: Three new acetophenone glycosides (1 -3 ) together with five known acetophenones were obtained from the roots of Euphorbia fischeriana, two (7, 8 ) of which displayed moderate inhibitory effect against Mycobacterium Smegmatis . Highlights: Three new acetophenone glycosides (1 -3 ) were obtained from the roots of Euphorbia fischeriana . Compound7 and8 displayed weak inhibitory effects against Mycobacterium smegmatis . All compounds were found to be inactive on the six human cancer cell lines used. Abstract: An extract of the Euphorbia fischerian root, used in the preparation of "Jieheling tablets" in China, exhibited bioactivity toward lymphoid tuberculosis and pulmonary tuberculosis. The present investigation identified three new acetophenone glycosides (1 -3 ), and five known acetophenones (4 -8 ). Materials were purified via chromatography and identified through spectroscopic analysis. Additionally, the potential anti-tuberculosis effects of the isolated acetophenones were evaluated using a Mycobacterium smegmatis model. Compounds7 and8 displayed weak inhibitory effects against Mycobacterium smegmatis, with MIC values of 0.1 and 0.2 mg/ml, respectively, being observed. All compounds were inactive when tested their cytotoxic activity on six human cancer cell lines.